Application of Analytic Hierarchy Process and Structural Equation Modeling for Supporting the Decision-Making of Shuttering Preference in Construction Projects - Vu Hong Son Pham; Thuy Dau; Le Tran (Journal of Soft Computing in Civil Engineering)
Shuttering is a temporary mold or structure into which concrete is poured and shaped. The choice of formwork can significantly impact the construction process, timeline, cost, and quality of the final structure. Certainly, identifying the most important criteria for selecting formwork (shuttering) is a valuable endeavor for supporting contractors in making informed decisions. This study is motivated by using the Analytic Hierarchy Process (AHP) to assess shuttering alternatives based on the identified evaluation criteria from the prior factor analysis stage. In addition, the Structural Equation Modelling (SEM) approach is employed to discover underlying relations between the latent factors of the model base on using a combination of statistical data and qualitative causal assumptions. The study reveals that plastic shuttering as the optimal solution according to expert evaluations and verified the hypothetical causal relations among the latent variables. The study's outcomes are intended to enhance managers' understanding of shuttering systems, promoting the adoption of decision support tools in construction projects for improved planning accuracy and project success.